2021
DOI: 10.1155/2021/5557947
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Palliative Care and Associated Factors among Nurses in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Palliative care is a multidisciplinary team-based care for patients facing life-threatening illness and their families which addresses their physical, psychological, social, and spiritual needs to improve the quality of care. There is a strategy for an increase in palliative care services by integrating with the healthcare system. Therefore, this systematic review and meta-analysis was aimed to assess the overall pooled prevalence of nurses’ knowledge towards palliative care in Ethiopia. Method. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Working experience was another predictor of caregivers' knowledge of and attitude toward PC that has been confirmed in previous studies (Fauziningtyas R 2020;Getie et al, 2021). More working experience is associated with more experience which will eventually lead to an increased level of knowledge (Eshaghian-dorcheh et al, 2019).…”
Section: 7supporting
confidence: 63%
See 1 more Smart Citation
“…Working experience was another predictor of caregivers' knowledge of and attitude toward PC that has been confirmed in previous studies (Fauziningtyas R 2020;Getie et al, 2021). More working experience is associated with more experience which will eventually lead to an increased level of knowledge (Eshaghian-dorcheh et al, 2019).…”
Section: 7supporting
confidence: 63%
“…The results also show that as the level of education increases, caregivers' attitudes and knowledge regarding PC improves. In a systematic review, health care providers with a bachelor's degree had a higher level of PC knowledge compared to those with diploma certificates (Getie et al, 2021). In Iran, some nursing master's programs briefly present materials regarding the concepts of nursing care provision for the patient and family in critical and end-of-life stages, death, mourning and grief, pain, emotional support of the patient and family and legal issues (Ebadinejad et al, 2021).…”
Section: 7mentioning
confidence: 99%
“…14 Healthcare professionals particularly nurses should be professionally prepared with education about the standards of palliative care to improve their knowledge and their roles in providing palliative care, in addition to the therapeutic relationship with patients and their families. 15 The lack of adequate knowledge about palliative care is considered the major barrier to the development and practice of palliative care. 16 Previous studies have found that nurses had a lack of knowledge about palliative care in different countries including the US, 17 Greece, 18 Mongolia, 19 Pakistan, 20 Nigeria, 21 Ethiopia, 22 and Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…23 A lack of nurses' knowledge about palliative care could lead to suboptimal quality and high cost of care. 15,24 Furthermore, previous studies found that nurses had poor knowledge about palliative care due to socio-demographic factors including age, 21,25 gender, 26,27 level of education, years of nursing experience, inadequate training in palliative care (pain and symptom management and therapeutic communication about care goals), and hospital ward (eg, critical care units, medical, and surgical). 15,17,19,23,[28][29][30][31][32] The World Health Organization established a public health strategy (PHS) as an effective approach to incorporating palliative care into the country's healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care is aimed to improve the quality of life of patients and their families in facing the problems associated with life-threatening diseases. It involves prevention, reduction, early diagnosis, and accurate assessment and treatment of pain and suffering as well as other physical, psychological, social, and spiritual problems [2]. A palliative care approach should be taken into account for people with cancer or any progressive or chronic illness as soon as the diagnosis of a life-threatening illness.…”
Section: Introductionmentioning
confidence: 99%